Yoga Therapy: A Boon for People Living with Cancer - Nair, Tushara; Kumar, G.P. (Disease and Health: Research Developments Vol. 9, 2025)
Cancer is one of the most common causes of death worldwide. Most of the patients with cancer have to undergo a long-term treatment protocol which includes surgery, radiotherapy, and chemotherapy. Many complications result because of cancer and its treatment, like cancer pain, cancer-related fatigue, stress, anxiety, and depression. All these complications reduce the quality of life of the patients living with cancer. Yoga is an ancient Indian Science that works on the mind-body concept, helping to maintain homeostasis in the body by regulating the autonomic nervous system. It includes asanas, pranayamas, and meditation. This helps in reducing the cancer pain, fatigue, stress, anxiety, and depression. All these factors help in improving the Quality of Life and mortality of the cancer patients. This chapter mainly focuses on providing insights into how yoga therapy is helpful for people living with cancer. In conclusion, yoga therapy, which is focused on mind-body concepts, is very helpful in reducing pain, anxiety, depression, and fatigue in cancer patients. This, in turn, becomes helpful in improving the quality of life and mortality of cancer patients.